A STUDY ON JOB SATISFACTION OF HIGHER SECONDARY SCHOOL TEACHERS AT TRICHY. - Kalaiselvan, D.D. (IJRDO - Journal of Social Science and Humanities Research, 2017)
Teachers are the backbone of the educational process and play a vital role in building the ation. Teachers act as a pivot around which all the educational programmes rotate and they are crucial in the implementation process also. It is also a fact that the quality of teachers influences the level of achievement of students. Gender has a bearing on the level of job satisfaction of higher secondary school teachers. There is no significant difference in the job satisfaction of schools with respect to the locality. Age has no bearing on the level of job satisfaction of higher secondary school teachers.